SAPIR-WHORF HYPOTHESIS: THE IMPACT OF LINGUISTIC RELATIVITY ON HUMAN THOUGHT AND WORLDVIEW - Matluba Tursunova (The Conference Hub, 2025)
This paper explores the Sapir-Whorf hypothesis, which suggests that language influences cognitive processes and perception. By analyzing empirical research and cross-linguistic studies, the paper examines how different linguistic structures shape thought patterns and worldviews. The discussion also considers criticisms of linguistic determinism and highlights the practical implications of linguistic relativity in artificial intelligence, education, and cross-cultural communication.